Regulation of the HIF switch in human endothelial and cancer cells - Jakub Slawski; Maciej Jaśkiewicz; Anna Barton; Sylwia Kozioł; James F. Collawn; Rafał Bartoszewski (European Journal of Cell Biology, 2024)
Hypoxia-inducible factors (HIFs) are transcription factors that reprogram the transcriptome for cells to survive hypoxic insults and oxidative stress. They are important during embryonic development and reprogram the cells to utilize glycolysis when the oxygen levels are extremely low. This metabolic change facilitates normal cell survival as well as cancer cell survival. The key feature in survival is the transition between acute hypoxia and chronic hypoxia, and this is regulated by the transition between HIF-1 expression and HIF-2/HIF-3 expression. This transition is observed in many human cancers and endothelial cells and referred to as the HIF Switch. Here we discuss the mechanisms involved in the HIF Switch in human endothelial and cancer cells which include mRNA and protein levels of the alpha chains of the HIFs. A major continuing effort in this field is directed towards determining the differences between normal and tumor cell utilization of this important pathway, and how this could lead to potential therapeutic approaches.